Clinical case: observation of a child with Chediak-Higashi syndrome - L. U. Ulukhanova; D. C. Amirkhanova; S. M. Attaeva; M. A. Ninalalov; N. C. Karnaeva (LLC "Diagnostics and Vaccines", 2023)
Chediak-Higashi syndrome is a rare immunodeficiency condition with generalized cellular dysfunction, with an autosomal recessive type of inheritance. Mostly young children suffer, death caused by infections or malignant neoplasms often occurs before they reach the age of 10 years. We describe a case of infectious mononucleosis caused by Epstein-Barr virus in a 3-year-old boy against the background of a rare hereditary Chediak-Higashi syndrome with the development of hemophagocytic syndrome.